Structural and optical properties of Bi- and Sn-doped Sb2Se3 thin films prepared by thermal evaporation - Kok, Mediha; Ozturk, Yunus; Sait Kanca, M. (Springer, 2026)
In this study, Sb2Se3-based semiconductor thin films, both pure Sb2Se3 and those doped with Bi and Sn, were produced using the thermal evaporation method. The structural, morphological, and optical properties of the obtained films were investigated using XRD, SEM, and UV-Vis spectroscopy. While films without annealing exhibited an amorphous structure, significant crystallization was observed after annealing at 350 degrees C, especially at high doping levels. SEM analyses showed significant changes in surface morphology and grain structure depending on the doping level. Optical measurements revealed that absorption increased and the band gap changed with increasing doping level. The band gap for the undoped Sb2Se3 thin film was found to be 1.54 eV. An increase due to the Burstein-Moss effect was observed at low additive ratios, while band narrowing was observed at high additive ratios. The results obtained indicate that Bi and Sn additives improve the optoelectronic properties of Sb2Se3 thin films and hold potential for photovoltaic applications.
Keywords: Perovskite Solar-Cells